Building a Culture of Health - David Briggs (ACHSM, 2017)
Commentary and published research on the value of healthcare has become more evident in recent times. There has been a noticeable shift from the focus on efficiency of health systems and practice to a greater focus on what effectively works, or more so, what doesn't work. Health delivery systems struggle with increased demand on existing services and other health priorities remain underserviced. What do we need to do to better examine and understand what delivers value to people, communities, the health system and at the same time improves health outcomes? ........